Prevalence of and factors associated with treatment modification at first cycle in older adults with advanced cancer receiving palliative treatment. Issue 8 (November 2021) - Mohamed, Mostafa R.; Kyi, Kaitlin; Mohile, Supriya G.; Xu, Huiwen; Culakova, Eva; Loh, Kah Poh; Flannery, Marie; Obrecht, Spencer; Ramsdale, Erika; Patil, Amita; Dunne, Richard F.; DiGiovanni, Grace; et al.
Abstract: Introduction: Treatment toxicities are common in older adults with cancer and consequently, treatment modifications are sometimes considered. We evaluated the prevalence and factors associated with treatment modifications at the first cycle in older patients receiving palliative systemic treatment. Methods: Patients ( n = 369) from the GAP 70+ Trial (NCT02054741 ; PI: Mohile) usual care arm were included. Enrolled patients were aged 70+ with advanced cancer and ≥ 1 Geriatric Assessment (GA) domain impairment. Treatment modification was defined as any change from National Comprehensive Cancer Network guidelines or published clinical trials. Baseline variables included: 1) sociodemographic factors; 2) clinical variables; 3) GA domains; and 4) physician beliefs about life expectancy. Bivariate analyses and multivariable cluster-weighted generalized estimating equation model were conducted to assess the association of baseline variables with cycle 1 treatment modifications. Results: Mean age was 77.2 years (range: 70–94); 62% had lung or gastrointestinal cancers, and 35% had treatment modifications at cycle 1. Increasing age by one year (odds ratio (OR) 1.1, 95% confidence interval [CI] 1.0–1.2), receipt of ≥second line of chemotherapy (OR 1.8, CI 1.1–3.0), functional impairment (OR 1.6, CI 1.1–2.3) and income ≤$50, 000 (OR 1.7, CI 1.1–2.4) were independently associated with a higher likelihood of cycle 1 treatment modification. Conclusion: Treatment modifications occurred in 35% of older adults with advanced cancer at cycle 1. Increasing age, receipt of ≥second line of chemotherapy, functional impairment, and lower income were independently associated with treatment modifications. These findings emphasize the need for evidence-based regimens in older adults with cancer and GA impairments.